Homer in the Debate Between Celsus and Origen - Villani, Andrea (Revue d'Etudes Augustiniennes et Patristiques, 2012)
Abstract This study analyzes the presence of Homeric quotations in the Origenian apology Against Celsus in order to grasp the different functions they cover. They can be summarized as follows: first, the epic citations are sometimes used by the two opponents just as an ornamental tool which embellishes their prose; second, they serve as a support for an argument proposed; third, they reveal a pure polemic aim. The last paragraph, finally, deals with an example of another way of Homeric reception in a Christian environment, hidden behind the lines of the text: indeed, also the prosopological exegesis, created as a hermeneutical tool in order to better understand the meaning of difficult passages in Homer’s poems, can be taken as another form of the presence of Homer in Origen’s apology. Abstract Cette étude analyse la présence des citations homériques dans l’apologie Contre Celse d’Origène, afin d’en dégager les différentes fonctions. Elles peuvent être réduites essentiellement à trois : les citations épiques apparaissent parfois seulement comme ornement stylistique de la prose de l’auteur qui l’emploie ; d’autres fois, elles sont utilisées comme soutien d’une argumentation ou d’une hypothèse ; enfin, elles peuvent avoir une fonction purement polémique. Le dernier paragraphe est consacré à un exemple, à lire entre les lignes, de la fortune d’Homère en milieu chrétien : en effet, l’exégèse prosopologique, telle qu’élaborée dans un milieu païen comme moyen d’interprétation des poèmes homériques, peut bien être considérée comme une autre forme de la présence d’Homère dans l’apologie d’Origène.